Vitesse, réseau, vision : La malle poste-anglaise de Thomas de Quincey - Jean-Christophe Valtat (Conserveries Mémorielles)
Usually linked to Opium, the visionary romantic aesthetic of Thomas De Quincey, can also be refered to the technological mutations of the emerging industrial modernity. The English Mail-Coach, especially, can be regarded as seminal text about the memorial and cognitive effects of such mutations. The Mail-Coach both as a means of transportation and communication allows De Quincey to take into account two new dimensions of experience : unstoppable speed and a centralized communication network. Together, through the power and fatality they produce, these notions play an essential part in the updating of a sublime and visionary aesthetic, based on compressed perceptions of space and time.